PENGARUH MODEL PEMBELAJARAN COURSE REVIEW HORAY TERHADAP PEMAHAMAN KONSEP MATEMATIKA PADA PESERTA DIDIK SEKOLAH DASAR - Mutaqin, Ejen Jenal; Yulia, Rini; Suryaningrat, Eko Fajar (Jurnal Inovasi dan Teknologi Pendidikan, 2023)
The Effect of Course Review Horay Learning Model on Understanding Mathematics Concepts of Fifth Grade Students at SDN 6 Cibunar Kec. Cibatu Kab. Garut Academic Year 2021/2022 This study aims to determine the effect of learning mathematics with the Course Review Horay model on the understanding of students' concepts in Class V SDN 6 Cibunar. This type of research is a pre-experimental one group pretest - posttest design. This research was conducted at SDN 6 Cibunar, Cibatu sub-district, Garut district with 20 students as the subject of the study as fifth grade students. Based on research conducted by researchers and the results of data processing and analysis of pretest normality test scores because ^2 count (4.17) <χ^2 table (7.81), then the data is normally distributed. While the posttest score for ^2count (7.47) <χ^2table (7.81), then the data is also normally distributed. Meanwhile, in hypothesis testing, it is obtained that t_count> t_table is 5.63> 2.03 so that it falls in the rejection area H_0 and is in the acceptance area H_1 in this case the hypothesis submission is accepted